A stepwise mechanism for the permeation of phloretin through a lipid bilayer (The Rockefeller University Press, 1982)
The thermodynamics of interactions between phloretin and a phosphatidylcholine (PC) vesicle membrane are characterized using equilibrium spectrophotometric titration, stopped-flow, and temperature- jump techniques. Binding of phloretin to a PC vesicle membrane is diffusion limited, with an association rate constant greater than 10(8) M-1s-1, and an interfacial activation free energy of less than 2 kcal/mol. Equilibrium binding of phloretin to a vesicle membrane is characterized by a single class of high-affinity (8 micro M), noninteracting sites. Binding is enthalpy driven (delta H = -4.9 kcal/mol) at 23 degrees C. Analysis of amplitudes of kinetic processes shows that 66 +/- 3% of total phloretin binding sites are exposed at the external vesicle surface. The rate of phloretin movement between binding sites located near the external and internal interfaces is proportional to the concentration of un-ionized phloretin, with a rate constant of 5.7 X 10(4) M-1s-1 at 23 degrees C. The rate of this process is limited by a large enthalpic (9 kcal/mol) and entropic (-31 entropy units) barrier. An analysis of the concentration dependence of the rate of transmembrane movement suggests the presence of multiple intramembrane potential barriers. Permeation of phloretin through a lipid bilayer is modeled quantitatively in terms of discrete steps: binding to a membrane surface, translocation across a series of intramembrane barriers, and dissociation from the opposite membrane surface. The permeability coefficient for phloretin is calculated as 1.9 X 10(-3) cm/s on the basis of the model presented. Structure- function relationships are examined for a number of phloretin analogues.